The Effect of Economic Factors on Mental Disorder Resulting To Crime - Mir-Khalili, Seyed Mahmoud; Aavani, Milad (Asian Economic and Financial Review, 2014)
Nowadays, social criteria such as economic situation, educational degree, and marital status and so on play a significant role in individual development and growth in community. Lack of such parameters provides background for mental tensions of individual and consequently appears mental disorders. It becomes more important that prevalence of mental disorders arising from lack of culture and social pathologies will occur in case of not being preventive strategies. This research tries to investigate economic status of mental patients and effect on crime considering statistical society of Azadi Hospital. Research methodology is descriptive- analytical. Economic status of families at the time of crime would occur in experimental group is included; 10.60 % of weak, 29.80 % of lower middle, 40.40 % of middle, 19.10 % of good economic status. On the other hand, economic status among control group is 10.50 % for weak class, 31.60 % for low class, 42.10 for middle class and 15.80 % for up class of economic status, there is a meaningful difference between then upon data obtained.